Study on Strength and Stiffness of Meranti Wood Truss with Plywood Gusset Plate Connection and Lag Screw Fastener - Naomi Pratiwi; Johannes Adhijoso Tjondro (Department of Civil and Environmental Engineering, Faculty of Engineering, UGM, 2018)
Wooden truss could be one of the options to be used as structural element in both in building and bridge. Wooden truss overcomes the limitation of timber with great dimension with necessary strength. In this study, the wooden truss was designed with Meranti wood type with elasticity modulus of 10,520 MPa and specific gravity of 0.8. The timber used has cross-section size of 45 mm × 45 mm, with truss frame span of 2,445mm and height of 400 mm. The connection between the timbers was using 18 mm thick plywood with 6 mm lag screw fastener. The destructive testing that was conducted on 3 test samples showed a result that the strength of the truss was at an ultimate load of 31,042 N with a ductility ratio of 5.61. Numerical study of the truss’ stiffness with this connection model resulted in stiffness degree value of 0.94.